Traceología: identificación de las huellas de producción y modo de vida de los individuos de Ancón (800-1100 d. C.) - Melgar Tísoc, Emiliano Ricardo (2021)
This text shows the impact of the Wari Empire on the way of life of the local population at the coastal site of Ancon, through the analysis of non-specific bone stress, as well as the traceology of the manufacturing techniques of malacological and lapidary funerary objects. The research on 11 individuals from the Necropolis of Miramar corresponding to the end of the Middle Horizon (800-1100 AD) is presented and the characterization of 72 malacological and lapidary pieces with scanning electron microscope and experimental archaeology. The result of the bone analysis shows that the greatest vulnerability occurred in children under two years old and young male adults, while the neonates and infants having the greatest amount and variety of stone materials from different regions of the Central Andes and mollusks from tropical waters. Despite the diversity of origins, the craft production of these objects was homogeneous and standardized as a result of a local production, while the elites at Ancon had benefited from the acquisition and distribution of this items.